2007
DOI: 10.1158/0008-5472.can-06-2283
|View full text |Cite
|
Sign up to set email alerts
|

Combining Adoptive Cellular and Immunocytokine Therapies to Improve Treatment of B-Lineage Malignancy

Abstract: Currently, the lineage-specific cell-surface molecules CD19 and CD20 present on many B-cell malignancies are targets for both antibody-and cell-based therapies. Coupling these two treatment modalities is predicted to improve the antitumor effect, particularly for tumors resistant to single-agent biotherapies. This can be shown using an immunocytokine, composed of a CD20-specific monoclonal antibody fused to biologically active interleukin 2 (IL-2), combined with ex vivo expanded human umbilical cord blood-deri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…33,34 We reported that adoptively transferred T cells infiltrated pulmonary tumor nodules and eradicated established tumor metastases. 35 Using MHC class I-restricted TCR transgenic T cells from the OT-1 mouse, which are specific for the surrogate tumor Ag ovalbumin, our group also found that exogenous IL-2 promoted T-cell persistence after adoptive transfer, and donor CD8 þ T cells developed a memory phenotype based on CD44 and Ly6c expression.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 We reported that adoptively transferred T cells infiltrated pulmonary tumor nodules and eradicated established tumor metastases. 35 Using MHC class I-restricted TCR transgenic T cells from the OT-1 mouse, which are specific for the surrogate tumor Ag ovalbumin, our group also found that exogenous IL-2 promoted T-cell persistence after adoptive transfer, and donor CD8 þ T cells developed a memory phenotype based on CD44 and Ly6c expression.…”
Section: Discussionmentioning
confidence: 99%
“…97 Antibodies fused to a cellsignaling molecule (immunocytokines) comprise another increasingly recognized group of ICs with activity in hematologic malignancies. 98 A tetrameric interferon-a construct attached to veltuzumab showed promising activity in a lymphoma mouse xenograft model. 99 Drug and linker affect the efficacy and toxicity profile of ADCs.…”
Section: Adcsmentioning
confidence: 99%
“…(57,272,281) The CAR was modified to replace CD28 endodomain for CD137 endodomain as a synthetic cDNA sequence Identities of final ROR1R plasmids were distinguished from CD19R plamids by PmlI enzyme and pSBSO-SIM and pSBSO-FRA plasmids were distinguished by BsrGI enzyme (Figure 7).…”
Section: Via3 Chimeric Antigen Receptorsmentioning
confidence: 99%